Meningkatkan Kesiapsiagaan Bencana Siswa Menggunakan E-Modul Sains Berbasis Android dengan Pendekatan SETS - Himawan Putranta; Tutik Yuliatun; Kristina Uskenat; Andi Reski (Postgraduate, University of Mataram, 2026)
Schools become high-risk areas in the event of an earthquake. This study aims to determine the increase in students' disaster preparedness through Android-based science e-modules using the SETS approach. This quasi-experimental study was conducted with a pre-test and post-test control group design. The subjects of this study were 61 eighth-grade students at an Islamic junior high school in Yogyakarta, selected through purposive sampling. The data collection instrument in this study consisted of 10 multiple-choice test items assessing disaster preparedness indicators, including knowledge and attitude, policies and guidelines, disaster response plans, early warning systems, and mobilization. Data analysis in this study used the gain standard equation to see the increase in student disaster preparedness. The findings of this study indicate that the normality test results for the control and experimental classes, for both pre-test and post-test, are significant at the 0.05 level, indicating that the data in both classes are normally distributed. The results for the experimental class showed a 70% increase in student disaster preparedness, falling into the high category, while the control class was 50%, in the medium category. These findings indicate that using Android-based science e-modules with the SETS approach can significantly increase student disaster preparedness.